Ultrafast exciton dynamics in 2D in-plane hetero-nanostructures: delocalization and charge transfer. Issue 12 (10th March 2017) - Cassette, E.; Pedetti, S.; Mahler, B.; Ithurria, S.; Dubertret, B.; Scholes, G. D.
Abstract : The ultrafast dynamics in Cd-based 2D in-plane heterostructures is revealed by femtosecond optical spectroscopy. Abstract : In this article we study the ultrafast dynamics of excitons and charge carriers photogenerated in two-dimensional in-plane heterostructures, namely, CdSe–CdTe nanoplatelets. We combine transient absorption and two-dimensional electronic spectroscopy to study charge transfer and delocalization from a few tens of femtoseconds to several nanoseconds. In contrast with spherical nanocrystals, the relative alignment of the electron and hole states of CdSe and CdTe in thin 2D nanoplatelets does not lead to a type-II heterostructure. Following the excitation in CdSe or CdTe materials, the electron preferentially delocalises instantaneously over the whole heterostructure. In addition, depending on the crown material (CdTe versus CdTeSe), the hole transfers either to trap states or to the crown, within a few hundreds of femtoseconds. We conclude that the photoluminescence band, at lower energy than the CdSe and CdTe first exciton transition, does not result from the recombination of the charge carriers at the charge transfer state but involves localised hole states.